SIGNIFICANCE OF DETECTION OF FREE/TOTAL PSA RATIO AND OTHER BIOCHEMICAL PARAMETERS IN PATIENTS WITH BPH, CARCINOMA PROSTATE AND ITS CLINICOPATHOLOGIC CORRELATION - Joshi, S.; Tilak, M. A.; Jadhav, S. (International Journal of Medicine and Medical Research, 2021)
Background. Benign prostatic hyperplasia (BPH) can raise prostate-specific antigen (PSA) levels two to three times higher than the normal level. An increased PSA level does not indicate Prostate Cancer (PCa), but the higher the PSA level, the higher the chance of having PCa. Detection and treatment have been profoundly affected by the advent of Free/Total PSA ratio testing. Objectives. The aim of the study was to estimate free, total PSA levels and its ratio for serum levels of calcium, acid phosphatase and alkaline phosphatase in patients with BPH and PCa; to correlate clinical, biochemical and histopathological findings in the above patients. Methods. PSA levels were detected by Chemiluminescent assay; serum calcium – by Modified Arsenazo method; serum acid phosphatase – by Doumas et al method; and Alkaline phosphatase – by Lowry et al method. Results. Present study found high levels of total PSA in BPH and PCa. Levels of free PSA were high in BPH as compared to PCa rate. Free/Total PSA ratio is reduced considerably in PCa as compared to BPH. Serum acid phosphatase and alkaline phosphatase were considerably higher in PCa as compared to BPH. Serum calcium levels did not show significant difference in control and study groups. Conclusions. It was established that patients with PCa have a greater fraction of bound PSA and a lower percentage of free PSA than in those without PCa. Therefore, in clinical practice Free/Total PSA ratio helps clinicians to decide if a biopsy is necessary. Objectives: The study was carried out with the following objectives: to estimate free, total PSA levels and calculate Free/Total PSA ratio in patients with BPH and Carcinoma Prostate, to study the serum levels of calcium, acid phosphates, and alkaline phosphatase in patients with BPH and PCa. and to correlate clinical, biochemical and histopathological findings in the above patients. Methods. Free and total PSA levels were detected by Chemiluminescent assay; Serum Calcium was detected by Modified Arsenazo method. Serum acid phosphatase was detected by Doumas et al method and Alkaline phosphatase were detected by Lowry et al method Results: Present study found high levels of Total PSA in BPH and PCa. Levels of free PSA were high in BPH as compared to PCa ate. Free /Total PSA ratio is reduced considerably in PCa as compared to BPH. Serum acid phosphatase and alkaline phosphatase were slightly raised in PCa as compared to BPH. Serum calcium levels did not show a significant difference in control and study groups. Conclusion: We concluded that patients with PCa have a greater fraction of bound PSA and a lower percentage of free PSA than in men without PCa. There was a negative correlation found between the free/total PSA ratio and the histopathologic findings. The lower the ratio higher is the grade of malignancy. Therefore in clinical practice Free/Total PSA ratio helps clinicians to decide if a biopsy is necessary